2017
DOI: 10.18632/oncotarget.23478
|View full text |Cite
|
Sign up to set email alerts
|

CT volumetry for gastric adenocarcinoma: association with lymphovascular invasion and T-stages

Abstract: PurposeTo determine whether gross tumor volume of resectable gastric adenocarcinoma on multidetector computed tomography could predict presence of lymphovascular invasion and T-stages.ResultsGross tumor volume increased with the lymphovascular invasion (r = 0.426, P < 0.0001) and T stage (r = 0.656, P < 0.0001). Univariate analysis showed gross tumor volume could predict lymphovascular invasion (P < 0.0001). Multivariate analyses indicated gross tumor volume as an independent risk factor of lymphovascular inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 36 publications
5
13
1
Order By: Relevance
“…Two previous studies (18)(19) evaluated the CT volumetry correlation with T stage in GC and demonstrated that CT volumetry was capable of distinguishing T1 stage from higher T stages in GC, which was consistent with our ndings. The accuracies of differentiating T1 stage from higher T stages of the two previous studies were 95% and 80.7%, respectively (18)(19).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Two previous studies (18)(19) evaluated the CT volumetry correlation with T stage in GC and demonstrated that CT volumetry was capable of distinguishing T1 stage from higher T stages in GC, which was consistent with our ndings. The accuracies of differentiating T1 stage from higher T stages of the two previous studies were 95% and 80.7%, respectively (18)(19).…”
Section: Discussionsupporting
confidence: 92%
“…Two previous studies (18)(19) evaluated the CT volumetry correlation with T stage in GC and demonstrated that CT volumetry was capable of distinguishing T1 stage from higher T stages in GC, which was consistent with our ndings. The accuracies of differentiating T1 stage from higher T stages of the two previous studies were 95% and 80.7%, respectively (18)(19). The optimal cut off values of CT volumetry for differentiating T1 from higher stages derived from the two studies were 19.4 and 8.2 cm 3 (18)(19), respectively, which were both distinctly higher than the cutoff value noted in the present study (1.34cm 3 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In numerous previous studies, investigators tried to estimate tumor volume with imaging tools, such as computed tomography (CT), magnetic resonance imaging (MRI), positron emission tomography (PET)computed tomography (CT), and their results sought that it was contributing to poor prognosis of patients [20][21][22][23]. However, in these studies, errors with the actual tumor range, including the inability to measure in image studies according to tumor shape and pattern, cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, for advanced gastric cancer, the interactions between tumors burden and lymphovascular invasion would likely increase with increasing tumor volume. Therefore, as tumor volume increase, so would the probability of micrometastases migrating from the tumor through the lymphatic vessels, increasing the postoperative recurrence rate and resulting in poorer prognosis [20,24,25]. Moreover, for tumors that invade the serosa, thus penetrating the gastric wall, tumor size is likely associated with a larger area of serosal invasion, increasing the likelihood of intraperitoneal dissemination and poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%